Confirmatory Factor Analysis Compared with Principal Component Analysis to Derive Dietary Patterns: A Longitudinal Study in Adult Women. Issue 7 (20th May 2015) - Bédard, Annabelle; Garcia-Aymerich, Judith; Sanchez, Margaux; Le Moual, Nicole; Clavel-Chapelon, Françoise; Boutron-Ruault, Marie-Christine; Maccario, Jean; Varraso, Raphaëlle
Abstract: Background: Principal component analysis (PCA) has been used extensively to derive dietary patterns. We proposed to use confirmatory factor analysis (CFA) in the same context as PCA—as a one-step approach—to derive dietary patterns. Objectives: The first aim of this study was methodologic and was to compare dietary patterns derived with the use of PCA and CFA, used as equivalent one-step approaches. The second aim of this study was to study these patterns in association with individual characteristics and new adult-onset asthma. Methods: We included 30, 589 French women from the E3N (epidemiologic prospective cohort study of women from the MGEN national insurance plan) with 1177 reported cases of adult-onset asthma between 1993 and 2005. PCA and CFA were used in the same context, on 27 food groups, to derive dietary patterns. Associations between dietary patterns and adult-onset asthma were assessed by Cox proportional hazards models. Results: Whether we used PCA or CFA, 3 similar factors were found and labeled "Prudent, " "Western, " and "Aperitif." Correlations between patterns derived with the use of PCA and CFA were high. For the "Prudent" and "Aperitif" patterns, we observed comparable patterns in terms of associations with food groups, individual characteristics, and the onset of asthma. For the "Western" patterns, the one derived with the use of CFA was more related to an unhealthy diet than the one derived with the use of PCA, with higher correlations with the food groups "processed meat" (0.73 vs. 0.51) and "dough and pastry" (0.63 vs. 0.40), and negative associations with physical activity and with having parents who were farmers. Regarding associations with adult-onset asthma, a significant positive association was observed for the "Western" pattern derived with the use of CFA [multivariate RR for highest vs. lowest quintile: 1.30 (1.02, 1.67), P -trend: 0.03], whereas no association was reported when using PCA [RR: 1.14 (0.89, 1.47), P -trend: 0.40]. Conclusion: Although quite similar dietary patterns were derived with the use of PCA and CFA, this study supports the alternative use of CFA to PCA for the identification of dietary patterns in epidemiologic studies.